Chitosan-Based Coating with Antimicrobial Agents: Preparation, Property, Mechanism, and Application Effectiveness on Fruits and Vegetables - Yage Xing; Qinglian Xu; Xingchen Li; Cunkun Chen; Li Ma; Shaohua Li; Zhenming Che; Hongbin Lin (International Journal of Polymer Science)
Chitosan coating is beneficial to maintaining the storage quality and prolonging the shelf life of postharvest fruits and vegetables, which is always used as the carrier film for the antimicrobial agents. This review focuses on the preparation, property, mechanism, and application effectiveness on the fruits and vegetables of chitosan-based coating with antimicrobial agents. Chitosan, derived by deacetylation of chitin, is a modified and natural biopolymer as the coating material. In this article, the safety and biocompatible and antimicrobial properties of chitosan were introduced because these attributes are very important for its application. The methods to prepare the chitosan-based coating with antimicrobial agents, such as essential oils, acid, and nanoparticles, were developed by other researchers. Meanwhile, the application of chitosan-based coating is mainly due to its antimicrobial activity and other functional properties, which were investigated, introduced, and analyzed in this review. Furthermore, the surface and mechanical properties were also investigated by researchers and concluded in this article. Finally, the effects of chitosan-based coating on the storage quality, microbial safety, and shelf life of fruits and vegetables were introduced. Their results indicated that chitosan-based coating with different antimicrobial agents would probably have wide prospect in the preservation of fruits and vegetables in the future.